1998
DOI: 10.1128/.66.9.4100-4107.1998
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Newly Isolated Shiga Toxin 2-Converting Phage from Shiga Toxin-ProducingEscherichia coli

Abstract: Science 226: [694][695][696] 1984). In this study, we isolated two Stx2-converting phages, designated Stx2⌽-I and Stx2⌽-II, from two clinical strains of STEC associated with the outbreaks in Japan in 1996 and found that Stx2⌽-I resembled 933W, the previously reported Stx2-converting phage, in its infective properties for E. coli K-12 strain C600 while Stx2⌽-II was distinct from them. The sizes of the plaques of Stx2⌽-I and Stx2⌽-II in C600 were different; the former was larger than the latter. The restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…67, 1999 NOTES 6711 ongoing recombination within the lambdoid phage gene pool (reviewed in reference 10). Differences between Stx2-encoding phages from serotype O157 STEC isolates have been reported (6,22). Our results extend these findings to include Stx2-encoding phages derived from STEC of various serotypes, including O157, O145, O111, and O83.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…67, 1999 NOTES 6711 ongoing recombination within the lambdoid phage gene pool (reviewed in reference 10). Differences between Stx2-encoding phages from serotype O157 STEC isolates have been reported (6,22). Our results extend these findings to include Stx2-encoding phages derived from STEC of various serotypes, including O157, O145, O111, and O83.…”
supporting
confidence: 84%
“…Significant genomic divergence among Stx1-encoding phages isolated from different E. coli serotypes has been dem-onstrated by analysis of phage genome lengths and restriction fragment length polymorphisms (RFLP) (25). Recent studies have revealed some variation within O157-derived Stx2-encoding phages (6,22). In the present study, to assess the level of variation among Stx2-encoding phages derived from multiple STEC serotypes and its possible relevance to toxin regulation, we produced isogenic lysogens of seven different Stx2-encoding phages.…”
mentioning
confidence: 99%
“…The receptors for certain Stx2-converting bacteriophages in E. coli have been recently elucidated. They are the maltose-inducible outer membrane protein, LamB, which serves as the lambda receptor, and the outer membrane protein, FadL, involved in long-chain fatty acid transport (Watarai et al, 1998). S. dysenteriae 1 strains 60R and 60RchlorR1 and S. flexneri strains 2457T and M90T were therefore grown with added maltose to induce the lambda receptor (Watarai et al, 1998), then incubated with purified H19BCmR bacteriophage (see Experimental procedures).…”
Section: Lysogeny Of S Dysenteriae 1 With Stec Bacteriophagementioning
confidence: 99%
“…The progeny stx -converting phages may infect other E. coli strains after adsorbing to the outer membrane proteins including BamA (Watarai et al, 1998 ; Smith et al, 2007 ). BamA is essential for outer membrane protein biogenesis (Wu et al, 2005 ) and exists in all members of the Enterobacteriaceae family.…”
Section: Introductionmentioning
confidence: 99%